If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15 + -12n = n + 12 Reorder the terms: 15 + -12n = 12 + n Solving 15 + -12n = 12 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. 15 + -12n + -1n = 12 + n + -1n Combine like terms: -12n + -1n = -13n 15 + -13n = 12 + n + -1n Combine like terms: n + -1n = 0 15 + -13n = 12 + 0 15 + -13n = 12 Add '-15' to each side of the equation. 15 + -15 + -13n = 12 + -15 Combine like terms: 15 + -15 = 0 0 + -13n = 12 + -15 -13n = 12 + -15 Combine like terms: 12 + -15 = -3 -13n = -3 Divide each side by '-13'. n = 0.2307692308 Simplifying n = 0.2307692308
| log^3(12x+3)=5 | | 9=-9+17 | | 159=14x+19 | | f(x)=2x^5-14x^3-10x^2-4250find(5) | | x+2x=-36 | | 7x+(-2)=44 | | x/3-x/2=4 | | 9x=6318 | | x+(x+4)+(x+7)+(x+9)+(x+10)=60 | | 0.5(x-4)=80 | | (3b^2+2b-4)/(b-2) | | -7k/8=49 | | -7(2x+6)=70 | | 7x6+2x10/2 | | 7a-4a= | | 15+9x=6x+8x-20 | | 9-1+5= | | f=n/4+37 | | 10+4(3p+10)=16 | | 5a/6+2b/9 | | 3x^2-10x-17=0 | | (5b+4)-2(b-5)=7 | | 5x/6-x/3 | | 2x-16=-8 | | 21(5+-4)=43 | | 21(5+-4)=7 | | z^2+8z+16= | | b+2.35=9.78+2b+722 | | .3a-3.25=5.75 | | 20x^3+72x^2-140x=0 | | 6b^2-31b+35= | | 4d+5-6d=-11 |